Health literacy policy to promote public health in Europe. (13th November 2019) - Rowlands, G
Abstract: Background: Health literacy is gaining increasing attention as a means of promoting individual- community- and population-level health, and is key to delivery of the European Health 2020 policy. European policy frameworks promote a holistic approach to policy at multiple levels in society and across multiple arenas in every-day life. Methods: An evidence synthesis was undertaken to describe health literacy policies in the WHO European Region: their distribution, organizational levels, antecedents, actors, activities and outcomes, along with the factors influencing their effectiveness. Evidence was obtained by a scoping review of academic literature in English, Dutch and German and of grey literature in English, Dutch, German and Italian, supported by a Region-wide expert enquiry. Emerging findings were presented to representatives from 19 Member States of the Region to check for accuracy and omissions. Results: The report highlights much good health literacy policy-related activity, mostly in the health and education sectors. Fewer policy-related activities were identified in other areas, such as the lived environment, employment, the media, and digital health. Robust evaluation of policy-related activities was identified in some, but not all, policies. Conclusions: Suggestions are made for policy-makers to share good health literacy policy practice, and to further develop policy aims and activities across all societal areas. An additional need is the development of robust health literacy metrics to direct resources and monitor the effectiveness of policy activities.